An investigation of the essential health services available to Internally Displaced Populations (IDPs) in Northern Nigeria - Ekezie, Winifred Chinweoke (2019)
Background Since 2011, Nigeria has experienced major conflicts from the Boko Haram terrorist group in the north-east region. Over 20 million people have been affected and about two million were forced out of their homes to other countries as refugees or remained in the country as Internally Displaced Persons (IDPs). As of December 2015, the majority of IDPs had settled across 13 of the 37 states in the country, and about 19% (~418,000) lived in camps or camp-like settings. Prior to this conflict, the northern regions had very poor health indices including poor immunisation coverage of 14.2% compared to the national average of 51%. Among the IDPs, the most common health conditions and causes of deaths were related to infectious diseases and severe acute malnutrition. Limited evidence existed on the availability of health-related resources and the IDP health management processes. Also little was known on the perceptions of IDPs in respect to their health. This thesis aimed to review the accessibility and provision of essential health services available to IDPs living in camp-like settings in Northern Nigeria, from both user and provider perspectives. Observed practices were assessed in relation to the IDP health issues and internationally recommended standards.